EFEKTIFITAS RELAKSASI OTOT PROGRESIF TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI ESENSIAL - Endar Sulis Tyani; Wasisto ' Utomo; Yesi ' Hasneli N (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Hypertension is a disorder of the circulatory system that could cause a rise in blood pressure above the normal value, which exceeds 140/90 mmHg. The research aim to find out the effectivity of progressive muscle relaxation to blood pressure of patients with essential hypertension. This research use quasy experiment design with non equivalent group approach. This research was conducted in Puskesmas Tenayan Raya with 30 samples, which divided into 15 as experiment group and 15 as control group by using purposive sampling technic. Experimental group was given 15 minutes progressive muscle relaxation. The blood pressure was measured with digital sphygmomanometer and observation sheet. The analysis used univariate by using frequencies and percentage and bivariate by using dependent t test and independent t test. The result of this research showed mean degression of sistole and diastole blood pressure occur on experiment group about 10,07 mmHg and 6,27 mmHg and progressive muscle relaxation was lowering blood pressure on patient with essential hypertension. The statistical test show degression of blood pressure significant on experiment group with p value 0,000 (<0,05). This results could be as nursing of intervention in lowering the blood pressure on patient with essential hypertension.